A Comparative Study to Evaluate Two Types of Solvents for Dissolving Endodontic Sealer Pastes with a Base of Mineral Trioxide Aggregate – A Cone-Beam Computed Tomography Analysis (Journal of Hama University, 2024)
Successful root canal retreatment is related to removing as much as possible of the previous filling materials as their remnants in the root canal negatively affects cleaning, and acts as a physical barrier that hinders bonding between new obturation materials and the dentin. Despite many uses and indications of modern endodontic filling pastes based on mineral trioxide aggregate (MTA), their removal in the context of endodontic retreatment is considerd difficult, and studies that evaluate the efficacy of their removal is relatively small. The aim of this study is to compare the effect of two types of solvents (Hydrochloric acid 17% and orange oil) for removing two types of endodontic sealer pastes based on MTA (White MTA, MTA Fillapex Sealer).This study was conducted on forty single-rooted single-canaled lower premolars. The sample was divided into two main groups (n1 = n2 = 20) according to the type of sealer paste used in canal filling. Then, each main group was divided into two subgroups, each of which contained 10 teeth. The first subgroup used orange oil as a solvent, while the second subgroup used 17% hydrochloric acid as a solvent, while standardizing the use of the ProTaper Retreatment system for rotary instrumentation in all subgroups groups.Cone-beam Computed tomography (CBCT) radiographs were taken before and after attempting to remove the filling material from the root canals, and comparisons were made between study groups to evaluate filling material remnants. Statistical studies showed that there were no statistically significant differences between the studied groups (P>0.05), despite the superiority of hydrochloric acid in comparison to orange oil in removal efficiency regardless of the sealer paste used, and the percentage of sealer paste remnants and the time required to remove it was less when using White MTA compared to MTA FILLAPEX SEALER.We conclude that the use of 17% hydrochloric acid is more effective than orange oil as a solvent for removing mineral trioxide-based sealer pastes.